THE DOUBLE EXCESS OF THE NAME: Deconstructing the Metaphysics of Exodus - Rogozinski, Jacob (Science et Esprit, 2024)
Etienne Gilson called “metaphysics of the Exodus” the thought which affirms the identity of God and Being, a fundamental thesis of “Christian philosophy” since Augustine. It is indeed authorized by the word – “I am He who is” – addressed to Moses on Sinai, as it was transmitted through its Greek and Latin translations. Which seems to inscribe the God of Biblical Revelation in Western metaphysics understood as onto-theology. Such a “god” then exposes himself to the same fate – and the same decline – as that which affects the ontology inherited from the Greeks. However, this ontological understanding of the Word of the Bush has been challenged in various ways. Several authors, from Eckhart to Lacan, have seen in it a negative statement – “I am who I am” … and do not ask for more – , that is to say an enigma. The dominant trend of Jewish tradition has understood it, on the contrary, as the affirmation of a being-with, the promise of a covenant: “I will be with you as He who will always be with you”. Should we discover here, as Ricoeur suggests, a “nonGreek understanding of Being” where biblical Revelation would exceed the onto-theological determination of metaphysics? Couldn’t this statement have a more directly political meaning, that of a subversion of the self-affirmation of the Pharaoh’s power? Perhaps the text of Exodus 3 attests there is another excess, more radical, when he superimposes to the promise of the Covenant the revelation of a singular Name: that of an Other I whose call would thwart the anonymous neutrality of Being.